Inverting OII 83.4 nm dayglow profiles using Markov chain radiative transfer. Issue 11 (5th November 2016) - Geddes, George; Douglas, Ewan; Finn, Susanna C.; Cook, Timothy; Chakrabarti, Supriya
Abstract: Emission profiles of the resonantly scattered OII 83.4 nm triplet can in principle be used to estimate O + density profiles in the F 2 region of the ionosphere. Given the emission source profile, solution of this inverse problem is possible but requires significant computation. The traditional Feautrier solution to the radiative transfer problem requires many iterations to converge, making it time consuming to compute. A Markov chain approach to the problem produces similar results by directly constructing a matrix that maps the source emission rate to an effective emission rate which includes scattering to all orders. The Markov chain approach presented here yields faster results and therefore can be used to perform the O + density retrieval with higher resolution than would otherwise be possible. Key Points: The intensity of the resonantly scattered OII 83.4 nm dayglow emission can be effectively modeled using a Markov chain based model The Markov chain approach yields results similar to an iterative method The inverse problem of obtaining O + density profiles from EUV dayglow emissions can be solved using this model and Bayesian statistics